The Climate Crisis and the Church: A Landscape for Theological Education - Keesmaat, Sylvia C. (Toronto journal of theology, 2022)
Acknowledging that the climate crisis is the defining issue of our time, this paper argues that theological education needs to be attentive to the following in order to provide resources for the anxiety and grief that the community is coping with: 1) the biblical tradition of lament; 2) biblical texts that grapple with climate catastrophe; 3) the legacy of colonialism; 4) the possibility of resurrection hope. In addition, this paper suggests that traditional theological education is deeply implicated in our current climate crisis and briefly outlines how the curriculum would need to be refocused in order to realistically equip clergy to vigorously engage the challenges their communities are struggling with.